Neuropsychological Functioning in Users of Serotonergic Psychedelics – A Systematic Review and Meta-Analysis - Basedow, Lukas A.; Riemer, Thomas G.; Reiche, Simon; Kreutz, Reinhold; Majić, Tomislav (Frontiers in Pharmacology, 2021)
Background: Serotonergic psychedelics (SPs) like LSD, psilocybin, DMT, and mescaline are a heterogeneous group of substances that share agonism at 5-HT2a receptors. Besides the ability of these substances to facilitate profoundly altered states of consciousness, persisting psychological effects have been reported after single administrations, which outlast the acute psychedelic effects. In this review and meta-analysis, we investigated if repeated SP use associates with a characteristic neuropsychological profile indicating persisting effects on neuropsychological function. Methods: We conducted a systematic review of studies investigating the neuropsychological performance in SP users, searching studies in Medline, Web of Science, Embase, ClinicalTrials.gov, and EudraCT. Studies were included if they reported at least one neuropsychological measurement in users of SPs. Studies comparing SP users and non-users that reported mean scores and standard deviations were included in an exploratory meta-analysis. Results: 13 studies (N = 539) published between 1969 and 2020 were included in this systematic review. Overall, we found that only three SPs were specifically investigated: ayahuasca (6 studies, n = 343), LSD (5 studies, n = 135), and peyote (1 study, n = 61). However, heterogeneity of the methodological quality was high across studies, with matching problems representing the most important limitation. Across all SPs, no uniform pattern of neuropsychological impairment was identified. Rather, the individual SPs seemed to be associated with distinct neuropsychological profiles. For instance, one study (n = 42) found LSD users to perform worse in trials A and B of the Trail-Making task, whereas meta-analytic assessment (5 studies, n = 352) of eleven individual neuropsychological measures indicated a better performance of ayahuasca users in the Stroop incongruent task (p = .03) and no differences in the others (all p > .05). Conclusion: The majority of the included studies were not completely successful in controlling for confounders such as differences in non-psychedelic substance use between SP-users and non-users. Our analysis suggests that LSD, ayahuasca and peyote may have different neuropsychological consequences associated with their use. While LSD users showed reduced executive functioning and peyote users no differences across domains, there is some evidence that ayahuasca use is associated with increased executive functioning.